2013
DOI: 10.1007/s00265-013-1623-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet reflectance influences female preference for colourful males in the European serin

Abstract: Avian plumage colouration is one of the most impressive displays in nature and is frequently used as sexual signal. There is now considerable evidence that females consistently prefer males with the most elaborated colour displays. Bird colour vision expands into the ultraviolet (UV) range, which prompted several studies to test the importance of UV in mate choice, revealing that females are affected by the UV light component. These studies were mostly performed on structural plumage, whereas carotenoid-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…Results also showed that females preferred more colourful males, as in a previous study (Leitão et al . ), whereas maintenance behaviour did not influence female choice.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Results also showed that females preferred more colourful males, as in a previous study (Leitão et al . ), whereas maintenance behaviour did not influence female choice.…”
Section: Discussionmentioning
confidence: 82%
“…We calculated Saturation of the entire spectra as ( R max – R min )/MBr, and UV‐Chroma as the proportion of the difference between UV maximum reflectance and minimum reflectance relative to MBr:(RmaxUVRnormalmin)/MBr(formulae used in Leitão et al . and adapted from Montgomerie ). We then used an average across all body regions for each spectral measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Avian plumage coloration is one of the most impressive displays in nature and is frequently used as a sexual signal. For many species, females consistently show a preference for males with the most elaborate colour displays and plumage brightness correlates with some measure of male quality, such as disease resistance or capacity for parental care (Hill, ; Leitão et al ., ). Plumage coloration comes either from light refraction caused by the structure of the feather or from pigments.…”
Section: Other Considerationsmentioning
confidence: 99%
“…The European serin Serinus serinus , is a small, sexually dichromatic cardueline finch, with males displaying a yellow carotenoid‐based patch on crown and breast, which is a sexually selected trait (Leitão et al ) that signals health condition (Trigo and Mota ). We conducted a field study to investigate whether body condition, parasite load, and age correlated with carotenoid‐based plumage colouration in a natural population of serins, during pair formation and breeding.…”
mentioning
confidence: 99%